Behavioral counseling content for optimizing the use of buprenorphine for treatment of opioid dependence in community-based settings: a review of the empirical evidence. - Copenhaver, Michael M; Bruce, R Douglas; Altice, Frederick L (The American journal of drug and alcohol abuse, 2007)
There is growing empirical evidence of buprenorphine's effectiveness in treating opioid dependence in community-based settings in the U.S. Decades of research indicates that in order for buprenorphine to have a sizable effect, it must be appropriately supported by behavioral counseling. Studies to date have not established the optimal behavioral counseling content for supporting buprenorphine treatment. The objective of this article is: 1) to review evidence of the key treatment-relevant issues posed by opioid-dependent patients in community-based settings in the U.S.; and 2) to review behavioral counseling content that may optimize the use of buprenorphine for treating opioid dependence in such settings. Evidence points toward the use of behavioral counseling aimed at enhancing patients' motivation during treatment entry followed by an emphasis on improving coping/relapse prevention skills during the primary phase of treatment.
Keywords: Adaptation, Psychological; Buprenorphine; Cognitive Therapy; Combined Modality Therapy; Counseling; Humans; Methadone; Motivation; Narcotic Antagonists; Narcotics; Opioid-Related Disorders; Patient Dropouts; Recurrence; Substance Abuse Treatment Centers; Treatment Outcome; United States